Model Community-Based Health Management dalam Pengendalian Hipertensi di Wilayah Kerja Puskesmas Tanasitolo - Ruslang Ruslang; Anugerah Yanuar Azis; Muhammad Amaliah S; Nirmawati Darwis; Nurhikmah Wijaya; A. Rizky Amaliah (Lentera Pena Cendekia, 2026)
Hypertension is a public health problem that requires continuous management through the involvement of patients, families, health cadres, and healthcare professionals. This study aimed to analyze the effectiveness of the Community-Based Health Management Model in improving knowledge, hypertension control behaviors, medication adherence, and blood pressure control among hypertensive patients in the working area of Tanasitolo Public Health Center. This quantitative study employed a pre-experimental one-group pretest–posttest design. A total of 40 hypertensive patients were selected using purposive sampling. The eight-week intervention included patient identification, four community-based education sessions, blood pressure monitoring, and hypertension management assistance. Data were collected using questionnaires assessing knowledge, hypertension control behaviors, and medication adherence, while blood pressure was measured using a digital device. The approach positioned the community as an active partner in monitoring risk factors, adopting a healthy diet, performing physical activity, managing stress, and maintaining regular therapy. The results showed that mean knowledge scores increased from 61.25 to 82.75, hypertension control behavior scores from 58.40 to 77.65, and medication adherence scores from 60.15 to 79.80. Mean systolic blood pressure decreased from 158.45 mmHg to 143.20 mmHg, while diastolic blood pressure decreased from 94.75 mmHg to 87.30 mmHg. All variables showed statistically significant differences (p<0.001). The Community-Based Health Management Model effectively improved hypertension self-management and supported blood pressure control. This model may be developed as a community-based hypertension management approach in primary healthcare by continuously involving health cadres and families.